Improvement versus transformation - Engeström, Yrjö (Education & didactique, 2017)
Anthony S. Bryk’s (2015) article is a call for systematic and accelerated improvement of schools by means of networked improvement communities. “This approach respects the complexities involved in educating well while also affirming that important aspects of the work of schooling should follow standard protocols.” (Bryk, 2015, p. 474) While the general thrust...